Sequência didática: resumo escolar por meio de retextualização de artigo de divulgação científica - Valdirene Batista da Costa Lage (2020)
In this work, a didactic sequence (DS) of a school summary was elaborated by means of the retextualization of scientific articles, aiming at improving students' written and reading skills. In the DS, activities were developed in order to improve language skills that enable students’ appropriation of increasingly complex language practices. These skills, as proposed by Bronckart (1999), can be: action skills (adaptation to context and referent), discursive skills (discursive structuring) and linguistic-discursive skills (mastery of psycholinguistic, linguistic and discursive operations). The elaboration of a summary contributes to the understanding of the basic text, in this case, of a scientific article and the didactic sequence proposed by Schneuwly and Dolz (2004) constitutes a pertinent instrument to reach that end, together with the retextualization that institutes an approach of reading different from the traditional ones based on explicit or implicit questions provided by textbooks. The results show that the work developed generated changes, that is, new knowledge, for all the ones involved: language skills developed by the students; planning and preparation of didactic material, by the teacher. In addition, the results show that the work developed in Portuguese language classes can contribute to the development of other areas by promoting reading activities of scientific texts, aiming at students’ understanding of the context and the referent, its planning, the textualization and enunciative mechanisms.